ANALISIS TINGKAT KECENDERUNGAN ADIKTIF PENGGUNAAN MEDIA SOSIAL PADA SISWA - Ayu Jingga Arisa; Wiryo Nuryono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the level of social media addiction tendencies among students at Surabaya Junior High School. The study used a quantitative approach with descriptive methods. The study subjects were 89 students. The instrument used was a questionnaire with 26 statements whose validity had been tested, using a Likert scale of 1–4. Data were analyzed using descriptive statistics and categorized based on the score range. The results showed that 13% of students were in the high category, 75% in the medium category, and 11% in the low category. In general, the level of social media addiction tendencies was in the medium category. In addition, the majority of students used social media for more than 6 hours per day, indicating a potential risk of addictive behavior. These findings indicate the need for preventive efforts through increasing digital literacy, strengthening self-regulation, and mentoring from teachers and parents to ensure wiser social media use